A Brief Review of Probiotic Use. (The East and Central African Journal of Pharmaceutical Sciences, 2018)
Probiotic therapy refers to use of live microorganisms to treat human pathological disorders such as lactose intolerance and antibiotic induced superinfections. The critical point to be consideted is whether such administered microorganisms can remain viable and multiply in the gastrointestinal tract given that their nutrient and environmental condition requirements are very exacting. In this brief review, the authors discuss the use of probiotics from a historical perspective and conclude that their use especially in form of traditional fermented food products can be justified the controversy notwithstanding.
Keywords: Probiotic; Lactobacillus